2020
DOI: 10.3390/molecules25051163
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations and Assays of α-Glucosidase Inhibition Activity on Gallic Acid Cocrystals: Can the Cocrystals be Defined as a New Chemical Entity During Binding with the α-Glucosidase?

Abstract: Cocrystallization with co-former (CCF) has proved to be a powerful approach to improve the solubility and even bioavailability of poorly water-soluble active pharmaceutical ingredients (APIs). However, it is still uncertain whether a cocrystal would exert the pharmacological activity in the form of a new chemical entity, an API-CCF supramolecule. In the present study, gallic acid (GA)-glutaric acid and GA-succinimide cocrystals were screened. The solubility, dissolution rate and oral bioavailability of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 34 publications
(37 reference statements)
1
2
0
2
Order By: Relevance
“…The third compound, gallic acid, has recently been proposed as a potential inhibitor of this enzyme, alone or combined with acarbose. 50,51 The results displayed in Figure 6 support this finding and show that its inhibitory activity does not significantly differ from that of miglitol.…”
Section: ■ Results and Discussionsupporting
confidence: 70%
“…The third compound, gallic acid, has recently been proposed as a potential inhibitor of this enzyme, alone or combined with acarbose. 50,51 The results displayed in Figure 6 support this finding and show that its inhibitory activity does not significantly differ from that of miglitol.…”
Section: ■ Results and Discussionsupporting
confidence: 70%
“…All these results suggested that 1-galloyl-glucose, gallic acid, methyl gallate, 1,6-digalloyl-β- d -glucose, and 1,3,6-trigalloylglucose are potential α-glucosidase inhibitors. Previously, N. Xue et al 43 and R. Xu et al 44 reported that gallic acid and methyl gallate showed α-glucosidase inhibitory activities with IC 50 values of 2.79 mmol L −1 and 0.23 mg mL −1 , respectively. Moreover, the α-glucosidase inhibitory effect of 1,6-digalloyl-β- d -glucose was reported and its IC 50 was 0.16 mg mL −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen bindings (the main interaction), van der Waals forces as well as π-π interactions, which are noncovalent interactions are responsible for the development of cocrystals [9] . When the co crystal results from the conjugation an API with a pharmaceutically accepted excipient (known as co former), the resultant compound is known as pharmaceutical cocrystal [10] and as shown in Figure 1. [11] Advantages and limitation of cocrystals Owing to their advantages, cocrystals have become progressively widespread drug modifications.…”
Section: Definitionmentioning
confidence: 99%